Managing global supply chain capabilities: The role of information sharing / Sidah Idris - Sidah, Idris (2017)
Over the past decade, many global supply chains have experienced a shift in which large and emerging economies are playing prominent roles as exporters, with Asia represented as among the higher exporters of intermediate goods to European Union and North America. Within the context of Malaysia, the development and growth of the local manufacturing sector was so rapid since the late 1990s; with the industry account for a significant proportion of Malaysia‘s total exports. With increased uncertainty of global supply chains, export demand from the advanced economies is expected to be less buoyant. The integration of Malaysian into international markets entails the local firms to comply with stricter quality regulations and produce technology-intensive goods, which may impede their participation. The emerging trend of the Trans-Pacific Partnership Agreement (TPPA) further is expected to create more competition and challenges for the Malaysian local companies, as a result of the removal of impediments to trade, which would encourage greater imports. Both critics and supporters of the TPPA contest the Malaysia‘s readiness to take advantage of its export, as many of the key-sectors are low on value addition. Due to this reason, the local manufacturing firms need to be able to develop effective management practices to help them in competing globally and to be more secure in times of economic crisis. Despite the growing importance of developing countries‘ participation including Malaysia in global supply chains, majority of studies that explore how global supply chain competitiveness could be achieved are drawn from developed countries‘ perspectives. While there is a growing argument that development of information technology has expedited effective supply chain management, empirical evidence still remains inconclusive with numerous inconsistencies and contradictory findings on the potential benefits, indicating a possibility of mediator. Drawing upon the resource-based view (RBV), dynamic capability theory (DCT), and social exchange theory (SCT), this study develops an integrative framework determining the impact of supply chain capabilities on global supply chain competitiveness. This research also investigates the mediating role of information sharing in the relationship between the different global supply chain capability factors and global supply chain competitiveness. In order to validate the theories, cross-sectional data were collected from Malaysian firms involved in the manufacturing industry; and analysed through structural equation modelling (SEM) to determine the relationships established. The study demonstrates that local manufacturers perceive organisational-culture fit and logistics integration commitmentas a significant component that affect their global supply chain competitiveness. The role of information sharing as a mediator in this research also facilitate in explaining why many local firms engage in international businesses fail to gain global supply chain competitiveness despite of investing huge amount of resources in building information technology infrastructure, trusts and strategic relationships. As Malaysia is moving towards a knowledge-based economy, more advanced and innovative technology should be adopted to improve competitiveness. The quality of information exchanged could further be improved if they are also willing to share not only operational information, but also strategic information. This study offers theoretical contributions by demonstrating knowledge on the issues relating to global supply chain competitiveness from the perspectives of Malaysian home-grown companies and supports the proposal that information sharing plays a mediating role between the different dimensions of theories proposed towards global supply chain competitiveness in the manufacturing industry.